Food & farming in hot and cold places - "Penny, Malcolm" (Wayland, Hove, 1994)
Slash and burn cultivation - Rice farming - Hunters in snow and frozen sea - Saami reindeer herders - Fishing in the Tropics - Cattle or camels - Tropical plantations - Cash crops